O09.4 HIV and HCV among clients of female sex workers in dnipro, ukraine. (14th July 2019) - Becker, Marissa; Balakireva, Olga; Herpai, Nicole; Mishra, Sharmistha; Cheuk, Eve; Pavlova, Daryna; Leung, Stella; Isac, Shajy; Forget, Evelyn; Lorway, Robert; Mcclarty, Leigh; Cholette, Francois; et al.
Abstract : Background: Ukraine has the highest HIV and HCV rates in Europe. Initially driven by unsafe injection use, more recent studies have documented the ongoing transmission of HIV via unprotected sex work. This paper describes the profile of clients of female sex workers (FSWs) in eastern Ukraine and their HIV and HCV prevalence and risk factors. Methods: We conducted a cross-sectional bio-behavioural survey of clients of FSWs recruited from sex worker hotspots in Dnipro, Ukraine. Inclusion criteria was men aged 18 and older who purchased sex services from a FSW (N = 370). The prevalence of HIV and HCV among clients was determined by serology from dried blood spots. Descriptive statistics of socio-demographic and sexual behavior are presented with univariate analysis for association. Results: The median age of clients was 32 (IQR 27–38) and the median age at first purchase of sex was 22 (IQR 19–27). Thirty-three percent of respondents were living with a regular sex partner. The mean number of sex services purchased in the past 6 months was 4.85 (SD 3.50), from 4.11 (SD 2.95) different FSWs. A mean of 2.1 hotspots were visited in the past 12 months (SD 1.6). Fourteen (3.8%) respondents reported ever injecting drugs. Two hundred and eight (56.2%) clients had ever tested for HIV. HIV and HCV prevalence was 2.4% (9) and 6.5% (24) respectively, yet only 33% (3/9) of people living with HIV reported knowing their status. Binge drinking was associated with both HIV and HCV prevalence; 8.2% of widowed/divorced respondents tested positive for HIV (p=0.003). Conclusion: The HIV prevalence among clients is almost three times the general population in Ukraine. Further, the frequency of sex work visits and the high number of sex workers visited, suggests a diffuse network with potential for wide transmission of HIV and HCV. Disclosure: No significant relationships.